1999
DOI: 10.1093/humrep/14.7.1847
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro maturation of human oocytes from regularly menstruating women may be successful without follicle stimulating hormone priming

Abstract: This prospective randomized study investigated whether the developmental potential of in-vitro matured (IVM) human oocytes is improved by follicle stimulating hormone (FSH) priming before aspiration. Normally cycling women were recruited among couples referred for in-vitro fertilization or intracytoplasmic sperm injection because of male factor and/or tubal disease. In the first experiment, 20 women were randomly allocated to either no stimulation (n = 10) or stimulation for 3 days with rec-FSH (Gonal-F, Seron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
3
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(107 citation statements)
references
References 31 publications
4
93
3
7
Order By: Relevance
“…Many researchers have shown increased number of oocytes collected and the maturation potential of these oocytes with FSH treatment in patients without PCOS (35) , and in patients with PCOS (36) . However, other studies of FSH treatment revealed no increase in maturation, fertilization or pregnancy rates in these two groups (37,38) . Fadini et al recently prospectively administered different gonadotropins, prior to the oocyte pick-up process (32) .…”
Section: Oocyte Pick-upmentioning
confidence: 61%
“…Many researchers have shown increased number of oocytes collected and the maturation potential of these oocytes with FSH treatment in patients without PCOS (35) , and in patients with PCOS (36) . However, other studies of FSH treatment revealed no increase in maturation, fertilization or pregnancy rates in these two groups (37,38) . Fadini et al recently prospectively administered different gonadotropins, prior to the oocyte pick-up process (32) .…”
Section: Oocyte Pick-upmentioning
confidence: 61%
“…It has been indicated that FSH priming with a fixed dose (150 IU/day) for 3 days from day 3 of the menstrual cycle does not increase the number of oocytes obtained per aspiration and does not improve oocyte maturation, cleavage rates or embryo development when women with normal cycling ovaries are treated (7). However, it has been reported that priming with recombinant FSH during the follicular phase before harvesting of immature oocytes from women with PCOS improves the maturational potential of the oocytes and the implantation rate of the cleaved embryos (8).…”
Section: Discussionmentioning
confidence: 99%
“…Ample evidence has shown that hCG priming enhances oocyte maturation and clinical pregnancy rates, while evidence for FSH priming remains limited; however, because FSH is believed to improve follicular health and to increase the quantity and quality of oocytes, especially in PCOS patients, some studies continue to include this step while others have removed FSH priming from their protocols [78,80,[82][83][84][85]. By investigating these topics, the obstacles of lower implantation and maturation rates may be overcome.…”
Section: Progress Of Ivfmentioning
confidence: 99%
“…At the present, there is limited data on using IVM with IVF in normo-ovulatory women as well as the implantation and pregnancy rates as compared with conventional IVF [88]. The relatively few studies published indicate not only decreased embryo quality and viability but also a significantly lower implantation rate following IVM with IVF versus that of conventional IVF [8,77,78,83]. While advances have been made as to improving IVM protocol and ensuring better success with embryo transfer, due to the nature of patients undergoing IVM significantly larger numbers of embryos are needed for transfer to ensure comparable rates to IVF [9,89].…”
Section: Choosing Ivmmentioning
confidence: 99%